Corelation of Multiple Intelegence Profiles on Initial Conditions of Plant Anatomy Practicum to the Needs of a Blended Learning Digital Microscope - S Sugianto; A Fitriani; S Angraeni; W Setiawan (Mangifera Edu, 2020)
The practice of plant anatomy using a light microscope indicates the immeasurable diversity of students' intelligence in making observations, such as logical-mathematical intelligence, visual-spatial intelligence, bodily-kinesthetic intelligence, and naturalistic intelligence. The population of this study were 35 prospective biology education teacher candidates, a sample selected using Purposiv Sampling, citing the limited number of samples. This study uses a questionnaire response instrument to determine the response of multiple intelligence profile of the initial conditions of plant anatomy practicum and blended learning digital microscope needs profile. All instruments are in the valid and reliable categories. Data analysis of the relationship between multiple intelligence profiles on the initial conditions of plant anatomy practicum to the needs of a blended learning-based digital microscope was analyzed quantitatively by Pearson's bivariate correlation test. Compound intelligence profile at the initial conditions of plant anatomy practicum has a low criterion, the profile of students' needs for blended learning digital microscope has high criteria, and there is a significant relationship between the profile of compound intelligence at the initial condition of plant anatomy practicum towards the needs of a blended learning-based digital microscope.